Innovation and entrepreneurship : a new mindset for emerging markets - Corrales-Estrada, Martha (Emerald Publishing Limited, 2019)
In the 21st Century, innovation is the key to entrepreneurial success. And in the fast-paced economy of Latin America, you have to innovate to compete.Innovation and Entrepreneurship: A New Mindset for Emerging Markets presents a combination of conceptual foundations, methodologies and tools to be applied in mini-cases and business challenges. Along with a cast of expert contributors including academics, global consultants and senior executives, editor Martha Corrales-Estrada explores how to transform the mindset of potential entrepreneurs and innovators in emerging markets. Looking across social and technological megatrends, Innovation and Entrepreneurship explores how to fill the unmet needs of new business opportunities with innovative and sustainable business models, including feasibility, desirability and viability perspectives and from personal, economic, pragmatic and social value creation domains.Including mini-cases and business challenges with actual examples of companies in emerging markets, this is an unmissable text for any business student, and particularly those in Latin America looking to analyse and deliver innovative solutions.